Amentoflavone Affects Epileptogenesis and Exerts Neuroprotective Effects by Inhibiting NLRP3 Inflammasome - Rong, Shikuo; Wan, Ding; Fan, Yayun; Liu, Shenhai; Sun, Kuisheng; Huo, Junming; Zhang, Peng; Li, Xinxiao; Xie, Xiaoliang; Wang, Feng; Sun, Tao (Frontiers in Pharmacology, 2019)
Brain inflammation is one of the main causes of epileptogenesis, a chronic process triggered by various insults, including genetic or acquired factors that enhance susceptibility to seizures. Amentoflavone, a naturally occurring biflavonoid compound that has anti-inflammatory effects, exerts neuroprotective effects against nervous system diseases. In the present study, we aimed to investigate the effects of amentoflavone on epilepsy in vivo and in vitro and elucidate the underlying mechanism. The chronic epilepsy model and BV2 microglial cellular inflammation model were established by pentylenetetrazole (PTZ) kindling or lipopolysaccharide (LPS) stimulation. Cognitive dysfunction was tested by Morris water maze while hippocampal neuronal apoptosis was evaluated by immunofluorescence staining. The levels of nucleotide oligomerization domain-like receptor protein 3 (NLRP3) inflammasome complexes and inflammatory cytokines were determined using quantitative real-time polymerase chain reaction, western blotting, immunofluorescence staining, and enzyme-linked immunosorbent assay. Amentoflavone reduced seizure susceptibility, minimized PTZ-induced cognitive dysfunction, and blocked the apoptosis of hippocampal neurons in PTZ-induced kindling mice. Amentoflavone also inhibited the activation of the NLRP3 inflammasome and decreased the levels of inflammatory cytokines in the hippocampus of PTZ-induced kindling mice. Additionally, amentoflavone could alleviate the LPS-induced inflammatory response by inhibiting the NLRP3 inflammasome in LPS-induced BV2 microglial cells. Our results indicated that amentoflavone affects epileptogenesis and exerts neuroprotective effects by inhibiting the NLRP3 inflammasome and, thus, mediating the inflammatory process in PTZ-induced kindling mice and LPS-induced BV2 microglial cells. Therefore, amentoflavone may be a potential treatment option for epilepsy.